IDENTIFYING UPPER MIOCENE – LOWER PLIOCENE LACUSTRINE SEDIMENTS IN DRY TUNKA BASIN OF THE BAIKAL RIFT ZONE - A. Hassan; S. V. Rasskazov; I. S. Chuvashova; T. A. Yasnygina; L. A. Titova; N. V. Kulagina; M. V. Usoltseva (Геодинамика и тектонофизика)
We present results of lithogeochemical, diatomic and palynological studies of sediments from the Tunka-13 well that was drilled in the southeastern part of dry Tunka basin in the Baikal rift zone. At the base of the section, there is an eroded basaltic flow of 16–15 Ma. From lithogeochemical signatures, we identify nine sedimentary units. The seven lower ones (interval 7.2–86.5 m) belong to the Tankhoi formation, the eighth (interval 2.7–6.6 m) to the Anosov formation, the ninth (interval <2.4 m) to the sandy stratum. We determined local sources of clastic material of basaltic and silicic compositions for units 1 and 2, respectively, and remote sources of silicic compositions for the overlaying units. The section shows a change from alluvial facies (units 1–3) through avandelta (unit 4) and lacustrine ones (units 5–7), again to alluvial facies (unit 8) and then to lacustrine-eolian ones (unit 9). Spore and pollen spectra from sediments of units 1–7 are divided into three palynozones (PZ), reflecting the vegetation change in the Late Miocene – Early Pliocene: PZ-1 – coniferous and deciduous forests with a small participation of thermophilic broadleaved species in moderately warm, humid climatic conditions; PZ-2 – enhancing the role of hemlock and more diverse thermophilic deciduous rocks in more humid and warm conditions; PZ-3 – a gradual reduction in the number of hemlock and other dark coniferous species, removing broad-leaved species by birch and alder, growing grassy communities in wetlands due to climate cooling. We identified layers of lacustrine facies by occurrence of fossil diatoms that are absent in the layers of the alluvial and avandelta facies. In lacustrine sediments, we distinguish four diatom zones: DZ-1 denotes a relatively deep Late Miocene paleolake, marked by planktonic species, DZ-2, DZ-3 and DZ-4 – a shallow Early Pliocene lake with a developed littoral zone and short transgression. The Late-Miocene paleolake transgression, indicated by changing facies, is associated with structural reorganization, accompanied by volcanic extinction in the Tunka valley about 9–8 Ma, and the Early Pliocene short transgression with a new reorganization, reflected in volcanic rejuvenation about 4.0 Ma.